Learning for leadership : a facilitative approach for training leaders - Hellman, Yael. (Alexandria, VA : American Society For Training & Development, 2014)
Teaching leadership can be one of the most fulfilling, as well as challenging, tasks of a trainer. Learning for Leadership builds on foundational learning and development concepts and practices to help trainers and facilitators develop programs that meet these challenges and turn learners into leaders. Yael Hellman illustrates how a truly "facilitative" classroom is structured, and she shows why it is the best environment to learn leadership skills. The author does so through the lens of group dynamics and her own experience facilitating leadership courses for the Los Angeles Police Department. The facilitative approach invites learners to practice leadership by being accountable for reaching learning objectives, taking initiative to solve problems, and nurturing their own ideas rather than leaning on authority.
Part I. Theories of leadership training : Learning leadership -- What makes a classroom facilitative? ; Group dynamics and facilitative training -- Part II. Beyond anecdote: measuring the effectiveness of facilitative training : Facilitative training in the private sector -- Facilitative training in the public sector -- Part III. Brass tacks handbook : Best practices and resources -- Experimential lesson outlines -- Wrapping it up -- Appendix: Effectiveness surveys for public or private sector training.
Includes bibliographical references and index.
Keywords: Executives -- Training of; Leaders -- Training of; Leadership -- Study and teaching